The Effect of Ratio o Wheat Starch and Breadfruit Flours with Kinds of Stabilizer on The Quality of Breadfruit Cookies - Kurnia A.K. Sitohang; Zulkifli Lubis; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Indonesia has imported much wheat  flour, therefore a replace of wheat flour is needed to be found. The aim of this research was to  find the effect of  wheat starch and breadfruit flours with kinds of stabilizer on the quality of breadfruit cookies. The research was using completely randomized design with two factors, i.e  ratio of wheat starch and breadfruit flour (S): (75%:25%), (60:40%), (45%:55%), (30%:70%) and kinds of stabilizer (P) : no stabilizer, gum arab, CMC and tween 20. Parameters analyzed  were water content, ash content, fat content, protein content, fiber content,  organoleptic value of flavor, taste, and texture. The results showed that the ratio of wheat starch and breadfruit flours had highly significant effect on the water content, ash content, protein content, fat content, fiber content, organoleptic value of flavor, taste, and texture. Kinds of stabilisizer gave highly significant effect on the water content,  organoleptic value of flavor, taste, and texture. The interaction of ratio of wheat starch and breadfruit flours with kinds of stabilizer gave significant effect on the organoleptic value of texture. The ratio of  wheat starch and breadfruit powder of 75%:25% and stabilisizer CMC (carboxy methyl cellulose)  gave the best quality of breadfruit cookies. Keywords : breadfruit flours, cookies, kinds of stabilizer, wheat starch